PEMANFAATAN FILLER ACKS DAN SUBSTITUSI PLASTIK KE DALAM ASPAL PADA CAMPURAN AC-WC - Roni Agusmaniza (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2020)
The quality of the asphalt mixture is very dependent on the composition of aggregate, asphalt and filler being used. The usual filler used in asphalt mixture is stone and ash fly ash. however, this filler is difficult to obtain and expensive. The palm oil shell ash (POSA) is expected to become the alternative. In addition, polimer modified asphalt can be used to improve the quality of asphalt mixtures. The polimer used was plastic wastes such as polyethylene terephthalate (PET), polystyrene (PS) and polypropylene (PP). this research aims to find out the use of POSA as filler and combination of plastic substitution into asphalt pen. 60/70 on AC-WC mixture. Manufacturing test object without and with the combination of plastic substitution amounted to 2.7%, 4.7%, 6.7% against the weight of asphalt on OAC ± 0.5% without and with filler POSA. The results showed that the use of plastic combination and filler POSA on AC-WC mixture can improve Marshall parameter value, especially the value of stability and MQ. The highest stability and MQ value obtained in 6.7% plastic combination with filler POSA on 5.81% asphalt content were at 2318.99 kg and 889.57 kg/mm. VIM and VMA value tended to increase by increasing plastics percentage into the asphalt and the use of POSA, whereas the values of density, VFA, and flow tend to decrease. The durability value of AC-WC mixture without and with plastic combination had met requirement, at ≥ 90%, while the use of ACKS as filler does not meet the requirements. Keywords: Asphalt Concrete-Wearing Course, POSA, Modified Asphalt, Plastic Waste Combination.